Selecting the right dose. Issue 8 (August 2013) - Avery, Tony; Gookey, Gill; Spencer, Rachel; Knox, Richard; Marsden, Kate; Salema, Ndeshi
Around one in six of the prescribing errors detected in the General Medical Council-funded PRACtICe study involved either the wrong dose or the wrong strength of medication. Around one in 10 of the prescribing errors involved giving a medicine at the wrong time. In this article we focus on the factors that need to be taken into consideration when selecting the right dose for an individual patient. We also highlight the importance of selecting the right timing for particular medicines. The article gives the reader opportunities to reflect upon different scenarios, and there are also suggestions for additional continuing professional development activities.